Fluid and carbohydrate replacement during exersice: How much and why? - Coyle, E. E. (1994)
1. During prolonged exercise in the heat, people can become dehydrated at a rate of 1-2 L every hour (about 2-4 lbs of body weight loss per hour). The rate of dehydration can be monitored by recording changes in nude body weight. Each pound of weight loss corresponds to 450 mL (15 fluid ounces) of dehydration. 2. Even a slight amount of dehydration causes physiological consequences. For example, every liter (2.2 lbs) of water lost will cause heart rate to be elevated by about eight beats per minute, cardiac output to decline by 1 L/min, and core temperature to rise by 0.3o C when an individual participates in prolonged exercise in the heat. 3. When it is important to minimize disturbances in cardiovascular function and body temperature and to reduce the perceived difficulty of exercise, people should attempt to drink fluids at close to the same rate that they are losing body water by sweating. 4. Unfortunately, runners generally drink only 300-500 mL of fluids per hour and thus allow themselves to become dehydrated at rates of 500-1,000 mL/h. Dehydration compromises cardiovascular function and places the runner at risk for heat-related injury. The runner must answer the question, Will the time I lose by drinking larger volumes of fluid be compensated for by the physiological benefits the extra fluid produces that may cause me to run faster during the last half of the race? 5. For an exerciser who weighs about 68 kg (150 lb), the requirements for both carbohydrate (i.e., 30-60 g/h) and fluid during prolonged exertion can be met by drinking 625-1,250 mL/h of beverages containing 4-8% carbohydrate. This volume must be adjusted for persons of different body weights. For example, an individual who weighs 50 kg should multiply the above recommendation by 50/68 or 0.74, i.e., 462.5-925 mL/h.